Digital inclusion finance, government subsidies and R&D investment—empirical evidence based on listed Chinese pharmaceutical firms - Zhao, XYv; Wang, Su; Chen, Yuwen (Frontiers in Public Health, 2025)
Digital inclusive finance, with ‘universality’ as its core feature, can stimulate enterprises to increase capital investment in research and development (R&D) through diversified channels. Using the digital financial inclusion index of 337 prefecture-level cities in China and the empirical data of Shanghai and Shenzhen A-share-listed pharmaceutical manufacturing enterprises from 2011 to 2022, the article empirically examines the impact mechanism of digital financial inclusion on R&D investment of pharmaceutical manufacturing enterprises from the perspective of government subsidy by using a high-dimensional fixed-effects model, a two-stage systematic GMM, and a moderated-effects test method. It is found that digital financial inclusion has a positive incentive effect on pharmaceutical manufacturing enterprises to increase R&D investment, and this positive effect still holds after the endogeneity test and robustness test. The results of the moderating effect test indicate that government subsidies play a positive moderating role in the process of digital financial inclusion affecting enterprises’ R&D investment. Further analyses show that digital financial inclusion has a more significant role in promoting the intensity of R&D investment in pharmaceutical enterprises in private enterprises, small and medium-sized enterprises, and regions with lower levels of traditional financial development. Finally, policy suggestions are put forward according to the conclusion. Including the government to promote digital infrastructure and policy support, financial institutions to build data platforms to support pharmaceutical innovation, and enterprises to increase investment in research and development and expand financing channels to jointly promote the transformation and upgrading of the industry.